Coordinate to Guard: Crosstalk of Phosphorylation, Sumoylation, and Ubiquitylation in DNA Damage Response - Kuo, Ching-Ying; Shieh, Christine; Cai, Fei; Ann, David K. (Frontiers in Oncology, 2012)
Small ubiquitin-like modifier-1/2/3 (SUMO-1/2/3) and ubiquitin share similar structure and utilize analogous machinery for protein lysine conjugation. Although sumoylation and ubiquitylation have distinct functions, they are often tightly associated with each other to fine-tune protein fate in transducing signals to regulate a wide variety of cellular functions, including DNA damage response, cell proliferation, DNA replication, embryonic development and cell differentiation. In this Perspective, we specifically highlight the role of sumoylation and ubiquitylation in ATM signaling in response to DNA double-strand breaks and hypothesize that ATM-induced phosphorylation is a unique node in regulating SUMO-targeted ubiquitylation in mammalian cells to combat DNA damage and to maintain genome integrity. A potential role for the coordination of three types of post-translational modification in dictating the tempo and extent of cellular response to genotoxic stress is speculated.